Corpus Christi : the birth and development of a late medieval feast (Pontificia Universidad Católica del Perú. Fondo Editorial, 1999)
Rituals and the religious festivals which accompany them are most usually encountered as 'traditional, long-standing phenomena, well-placed within the rhetoric of custom, authority and antiquity. They rarely have histories which those living them are aware, or that we, historians and anthropologists can trace. This is particularly true when one is studying any Christian feast.